APAKAH BEBAN PAJAK TANGGUHAN DAPAT DIGUNAKAN UNTUK MENDETEKSI MANAJEMEN LABA? - Tertiarto Wahyudi (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2012)
This paper evaluates the possibility of using deferred tax expense as an indicator todetect earnings management. If we assume GAAP allow greater discretion than taxationrules, and if we assume mangers exploit such discretion to manage income upward such away that does not affect taxable income, then the earnings management will generateaccounting-tax differences that increase deferred tax expense.Using data from the listed companies in the Jakarta Stock Exchange in fiscal yearof 2008, the result provides evidence that deferred tax expense is incrementally useful indetecting earnings management in the form of scaled earnings changes. In addition, totalaccruals and absolute abnormal accruals are also predictors for earnings management.